2019
DOI: 10.1371/journal.pone.0224517
|View full text |Cite
|
Sign up to set email alerts
|

Macmoondongtang modulates Th1-/Th2-related cytokines and alleviates asthma in a murine model

Abstract: ObjectiveMacmoondongtang has been used as a traditional medicine to treat pulmonary disease in Korea. However, the mechanism underlying its therapeutic effect has yet to be reported. In the present study, the role of macmoondongtang as a respiratory medicine, especially as an anti-asthmatic agent, has been attributed to the down-regulation of interleukin (IL)-4 and tumor necrosis factor (TNF)-α.Materials & methodsBALB/c mice were divided into five groups: control, asthma-induced control, dexamethasone treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Drugs for asthma treatment have a lot of adverse effects such as growth retardation [ 22 ], neurological disorders (e.g., catatonia, lack of concentration, and insomnia), and physiological disorders (e.g., immunosuppression, hypertension, hyperglycemia, and osteoporosis) [ 23 ]. Therefore, numerous studies have been conducted to identify safer and more effective anti-asthma drugs [ 4 , 8 , 13 , 17 , 18 , 28 ]. Korean Red Ginseng is known to affect various aspects of physiology, such as immunity [ 25 ], circulation [ 26 ], and inflammation [ 27 ], and diseases, such as allergy [ 28 ], cancer [ 29 ], metabolic diseases [ 30 ], and neurodegenerative diseases [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drugs for asthma treatment have a lot of adverse effects such as growth retardation [ 22 ], neurological disorders (e.g., catatonia, lack of concentration, and insomnia), and physiological disorders (e.g., immunosuppression, hypertension, hyperglycemia, and osteoporosis) [ 23 ]. Therefore, numerous studies have been conducted to identify safer and more effective anti-asthma drugs [ 4 , 8 , 13 , 17 , 18 , 28 ]. Korean Red Ginseng is known to affect various aspects of physiology, such as immunity [ 25 ], circulation [ 26 ], and inflammation [ 27 ], and diseases, such as allergy [ 28 ], cancer [ 29 ], metabolic diseases [ 30 ], and neurodegenerative diseases [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Korean Red Ginseng is known to affect various aspects of physiology, such as immunity [ 25 ], circulation [ 26 ], and inflammation [ 27 ], and diseases, such as allergy [ 28 ], cancer [ 29 ], metabolic diseases [ 30 ], and neurodegenerative diseases [ 31 ]. In asthma patient severe airway blockage was observed and this symptom was caused by airway remodeling which is related with epithelial cell and goblet cell hyperplasia, mucous hypersecretion by goblet cells, etc [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding pro-inflammatory cytokines, we did not find significant differences in IL-4 nor IL-13 levels. IL-4 is a cytokine related to the polarization of inflammatory profile to Th2 in lymphocytes; it is produced mainly by eosinophils, basophils, and mast cells [22,89]. IL-13 is produced by T-cells that accomplish function as promote cell growth and B-cells differentiation [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…This is the cases of the GLRcontaining Siji-kangbingdu herbal mixture, Maxing Shigan decoction and Lianhua-Qingwen capsules, used in China to treat upper respiratory infections (Jia et al, 2015;Yao et al, 2019). It is also the case for the GLR-containing traditional medicine Macmoondongtang used to treat pulmonary disease in Korea (Lee, Kang, Bok, Cho, & Park, 2019). Second, a clinical study performed in Japan in 2002 among military patients treated for upper respiratory tract infections (URTI) has shown that GLR therapy was associated with a shorter hospitalization, lower-grade fever and lower cost of therapy compared with controls.…”
Section: Glr and Respiratory Distress Syndromementioning
confidence: 99%